Relationship between propelling efficiency and swimming performance in elite swimmers - Huang, Z.; Kurobe, K.; Nishiwaki, M.; Ozawa, G.; Tanaka, T.; Taguchi, N.; Ogita, F. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: The propelling efficiency (ep) has been suggested as a important determining factor of competitive swimming (Toussaint, 1990). However, although there are several studies that investigated with respect to the metabolic capacity and drag in elite swimmers, propelling efficiency of elite swimmers has not been examined, and the relationship between propelling efficiency and swimming performance in elite swimmers has not been clarified, either. Therefore, this study aimed to examine the relationship between propelling efficiency and swimming performance in elite swimmers. METHODS: The subjects were 9 elite Japanese swimmers (age: 23±1 yrs) including a gold medalist and a finalist in Olympic Games. By the use of an extended version of the measurement of active drag which was developed by our laboratory, Pd was measured directly. Simultaneous measurement of oxygen uptake (VO2) enabled the establishment of the relationship between the rate of the energy expenditure (PVO2) and Po (since when swimming on the MAD system, Po=Pd). These individual relationships describing the mechanical efficiency (eg) were then used to estimate Po in free swimming from measurements of VO2. Since Pd was directly measured at each velocity studied by use of the MAD system, ep could be calculated according to the equation ep= Pd/(Pd+Pk)=Pd/Po. Also, a swimming performance of each subject was evaluated by swimming velocities which were calculated from the performance time of 50m, 100m, 200m and 400m maximal swimming. RESULTS: Mean value of swimming velocity of each distance was 1.82±0.05m/s in 50m, 1.70±0.04m/ in 100m, 1.58±0.06m/s in 200m and 1.52±0.06m/s in 400m, respectively. The mean values of eg and ep were 10±1% (range; 6 to 11%), and 71±6% (range; 56 to 80%), respectively. The individual ep values were significantly related to individual swimming performance in 200m and 400m (200m; r=0.72, P<0.05, 400m; r=0.80, P<0.01), but not to those in 50m and 100m. DISCUSSION: The findings of this study indicated that that ep observed in elite swimmer exceeds 70%, which is comparably higher than those reported previously. Also, the results suggest that ep is more important factor to determine swimming performance for middle and long-distance event rather than for short-distance event.